Clinical application of a novel hysteroscopic LNG-IUS non-suture fixation at the uterine fundus - Yu, Yi; Zhang, Hongwei; Sui, Long; Chen, Limei (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to explore the feasibility and clinical effects of a novel hysteroscopic levonorgestrel-releasing intrauterine system (LNG-IUS) non-suture fixation at the uterine fundus.MethodsFrom October 2023 to July 2024, a prospective study involving a novel hysteroscopic LNG-IUS non-suture fixation at the uterine fundus was conducted at Obstetrics and Gynecology Hospital, Fudan University. The patient’s clinical symptoms, surgical time, surgical complications, postoperative LNG-IUS expulsion, and other follow-up information were recorded.ResultsA total of 31 patients were included in this study. The average uterine depth is 9.17 ± 0.67 cm. Among them, 10 cases had a history of LNG-IUS expulsion. The average surgical time is 13.0 ± 4.1 min, and the average intraoperative blood loss is 5.3 ± 3.6 mL. All patients did not experience complications such as uterine perforation, massive bleeding, fluid overload, or postoperative infection. The average follow-up time after surgery was 6.0 ± 1.8 months, and no LNG-IUS expulsion occurred. The pain assessment and mean menstrual flow postoperation were less than preoperation, and the endometrial thickness and mean uterine volume postoperation were lower than preoperation, with statistically significant differences. For patients with dysmenorrhea, the postoperative relief rate was 96.3% (26/27), and for those with excessive menstruation, the postoperative effective rate reached 96.2% (25/26). The main adverse reaction was irregular vaginal bleeding, with an incidence rate of 61.3% (19/31).ConclusionHysteroscopic LNG-IUS non-suture fixation at the uterine fundus is a safe and effective technique, particularly suitable for patients with dysmenorrhea, excessive menstruation, or a large uterine cavity who have previously experienced LNG-IUS expulsion. This procedure is simple and minimally invasive, has a short surgical time, has minimal bleeding, and provides rapid recovery; therefore, it is worthy of clinical application.